2022
DOI: 10.1038/s43705-021-00084-2
|View full text |Cite
|
Sign up to set email alerts
|

Glycan profiling of the gut microbiota by Glycan-seq

Abstract: Bacterial glycans modulate the cross talk between the gut microbiota and its host. However, little is known about these glycans because of the lack of appropriate technology to study them. In this study, we applied Glycan-seq technology for glycan profiling of the intact gut microbiota of mice. The evaluation of cultured gram-positive (Deinococcus radiodurans) and gram-negative (Escherichia coli) bacteria showed significantly distinct glycan profiles between these bacteria, which were selected and further anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…To confirm the Glycan-seq data, lectins differentially detected in the cultured bacteria were subjected to flow cytometry analysis, the gold standard for cellular lectin staining. The results indicated that the identified lectins are bound to the bacteria, which is in agreement with the Glycan-seq data and suggested that Glycan-seq data may be applied to bacterial cell surface glycan analysis ( Oinam et al, 2022 ). The specific lectin binding was confirmed using a competition assay with saccharide inhibitors and glycosidase treatment, followed by flow cytometry.…”
Section: Glycan-seq Of the Gut Microbiotasupporting
confidence: 81%
See 4 more Smart Citations
“…To confirm the Glycan-seq data, lectins differentially detected in the cultured bacteria were subjected to flow cytometry analysis, the gold standard for cellular lectin staining. The results indicated that the identified lectins are bound to the bacteria, which is in agreement with the Glycan-seq data and suggested that Glycan-seq data may be applied to bacterial cell surface glycan analysis ( Oinam et al, 2022 ). The specific lectin binding was confirmed using a competition assay with saccharide inhibitors and glycosidase treatment, followed by flow cytometry.…”
Section: Glycan-seq Of the Gut Microbiotasupporting
confidence: 81%
“…Each colored bar represents the bacterial family identified. Figures are reprinted from Oinam et al (2022 ) ( Oinam et al, 2022 ).…”
Section: Glycan-seq Of the Gut Microbiotamentioning
confidence: 99%
See 3 more Smart Citations